Characteristics of Hospital Workers Using a Wellbeing Center Implemented During the COVID-19 Pandemic to Prevent the Emotional Impacts of the Crisis - d'Ussel, Marguerite; Adam, Frédéric; Fels, Audrey; Chatellier, Gilles; Philippart, François (Frontiers in Public Health, 2022)
Introduction: The COVID-19 pandemic has been a worldwide unprecedented challenge for healthcare workers and other hospital employees. Disruptions in work and personal life may have led to mental health problems. To prevent or limit the severity of such issues, a local initiative has been implemented in a French hospital: a dedicated lounge, also called “Bulle” (literally bubble, meaning safe space) has been set up to provide a quiet caring environment and health support. Other similar well-being centers have been implemented in other countries but very little data is available about their practical effectiveness. The purpose of our study was to assess what type of hospital workers have frequented the Bulle and describe their psychological state in terms of anxiety, depression, and post-traumatic stress disorder (PTSD) just after the first wave, compared to those who had not come to the Bulle. Methods: From July 15th to October 1st 2020, a cross-sectional survey had been conducted among all workers collecting demographic information, professional data (experience, satisfaction), emotional experience during the first wave of COVID-19, and psychological specificities including history of burn-out, or symptoms of anxiety, depression, and PTSD. We asked them if they had accessed the Bulle or not. Results: 675 employees (out of 2,408; 28.0 %) fully completed the survey. 199 respondents (29%) reported having accessed the Bulle during the first wave of the pandemic. Significant symptoms of anxiety, depression, and PTSD were reported by respectively 41%, 20%, and 14% of the participants. Logistic regression analysis did not show any relationship between the Bulle usage and the prevalence of later psychological symptoms. However, employees who benefit from the solicitation of the psychological support team in their hospital unit were secondary more prone to come to the Bulle (odds ratio [OR], 2.24; 95% confidence interval [95% CI]: 1.09; 4.59). Conclusions: Anxiety, depression and PTSD were common after the first part of the COVID-19 pandemic and the attendance of quiet and well-being space seemed to be easier with a proactive intervention of psychological teams directly inwards.